On platforms, incomplete contracts, and open source software - Andras Niedermayer (University of Bern, Department of Economics, 2007)
We consider a firm A initially owning a software platform (e.g. operating system) and an application for this platform. The specific knowledge of another firm B is needed to make the platform successful by creating a further application. When B's application is completed, A has incentives to expropriate the rents. Netscape claimed e.g. that this was the case with its browser running on MS Windows. We will argue that open sourcing or standardizing the platform is a warranty for B against expropriation of rents. The different pieces of software are considered as assets in the sense of the property rights literature (see Hart and Moore (Journal of Political Economy, 1990)). Two cases of joint ownership are considered beyond the standard cases of integration and non-integration: platform standardization (both parties can veto changes) and open source (no veto rights). In line with the literature, the more important a party's specific investments the more rights it should have. In contrast to Hart and Moore, however, joint ownership can be optimal in our setting. Open source is optimal if investments in the applications are more important than in the platform. The results are driven by the fact that in our model firms invest in physical (and not in human) capital and that there is non-rivalry in consumption for software.
Keywords: C70; D23; L13; L22; L86; 330; platforms; open source; standardization; incomplete contracts; property rights; joint ownership; Open Source; Standardisierung; Unvollständiger Vertrag; Immaterialgüterrechte; Spieltheorie